Application of Moringa Leaves (Moringa oleifera) in Liquid Organic Fertilizer for Red Spinach (Amaranthus tricolor L) Plant Growth - Fiddaroini, Saidun; Yulianti, Eny (Program Study of Biology, Science and Technology Faculty, UIN Maulana Malik Ibrahim Malang, 2023)
Industrial and social activities have a significant impact on environmental degradation, with soil pollution being one of the consequences. Consequently, plants are unable to achieve proper growth. One viable solution lies in the application of liquid organic fertilizer. Liquid organic fertilizer derived from naturally fermented Moringa leaves presents a potential remedy to this issue. Moringa leaf liquid organic fertilizer contains essential macronutrients (N: 4.02%; Ca: 12.3%; P: 1.17%; Mg: 0.10%; K: 1.8%; and Na: 1.16%), micronutrients (Zn, Fe, Cu), and growth hormones (zeatin and cytokinin), making it highly suitable for use as a liquid organic fertilizer. The study encompassed two variables, namely the impact of soil pH and the effect of liquid organic fertilizer derived from Moringa leaves over a span of 30 days. The findings revealed that red spinach plants failed to thrive in soil with a pH ranging from 3.5 to 4. However, when cultivated in soil with a pH of 4.5, they exhibited a lifespan of 7 days, while in soil with a pH of 5, growth could be sustained for 9 days. Red spinach demonstrated favorable growth rates at pH levels of 5.5, 6, 6.5, and 7, albeit at different rates. Notably, the height growth of red spinach plants, when watered with the addition of liquid organic fertilizer derived from Moringa leaves, proved to be 1.4 times faster compared to those without organic fertilizer. Furthermore, the length growth ratio of red spinach leaves, when treated with the aforementioned liquid organic fertilizer, exceeded that of plants without organic fertilizer by 1.375 times, highlighting the accelerated growth of Moringa leaves.